Several Factors Affecting Audit Judgment with Moral Reasoning Moderation - Rustan Rustan (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
The purpose of this study is to analyze and examine the effect on audit judgment of self-efficacy, obedience pressure, and moral reasoning. The purpose of this study is to analyze and examine the relationship between self-efficacy and obedience pressure using audit judgment as a moderator. The study population consisted of auditors employed by BPK RI Representatives in South Sulawesi Province who had audited local government financial reports for a period of more than five years. The total population is 52 auditors, and because the population is less than 100, the sample is determined using the census method. We gathered data for this study by sending questionnaires to all respondents. The Partial Least Squares (PLS) method was used to analyze the data. The findings indicated that self-efficacy, obedience, and moral reasoning all influenced audit judgment positively and significantly. Additionally, moral reasoning is incapable of moderating the relationship between self-efficacy and audit judgment; similarly, the moral sense is incapable of moderating the relationship between compliance pressure and audit judgment.